Passing the first year of university degree programs in times of pandemic: hinges and ruptures in the perception of students from the National University of La Plata, Argentina (Itinerarios Educativos, 2021)
This article presents preliminary results of an education research work that addresses students’ perceptions of their university experience in the critical stretch of the first year as regards online teaching and learning in the absence of on-site classes. For the construction of data, we developed a qualitative methodological strategy that met the requirements of the lockdown caused by the COVID-19 pandemic. The strategy was based on an online questionnaire being filled in by students in the first year of two social sciences programs at two different faculties of Universidad Nacional de La Plata, Buenos Aires, Argentina. The question of the senses built by students is an appropriate field for analyzing ‘what happens’ and ‘what happens to them’. The rupture of the known quotidian university life gives rise to new questions that deserve analysis. The perceptions of virtual university experiences include both strongly negative and highly positive assessments; in the middle of both types of appreciation, there are folds, cleavages, and shades that coexist and reveal the active and heterogeneous condition of students.
Keywords: university; first year; students’ perceptions; virtual experience